Clonal evolution revealed by next-generation sequencing in a long-term follow-up patient with hypereosinophilia. (2019) - Chen, Meiyu; Liu, Jie; Qin, Wei; Wang, Qian; Zhang, Ri; Chao, Hongying
Highlights: l Next generation sequencing (NGS) applied to establish clonality in a patient with hypereosinophilia. l The first study reported the clonal evolution in a long-term follow-up patient from CEL-NOS stage to MDS and s-AML. l Disease progression was associated with clonal evolution. Abstract: The natural history of primary hypereosinophilia remains poorly defined, given the underlying disease heterogeneity. Recently, targeted NGS helps to establish clonality in a subset of patients with hypereosinophilia. We first reported the clonal evolution in a long-term follow-up patient with hypereosinophilia. This case initially presented with chronic eosinophilic leukemia, not otherwise specified (CEL-NOS), successively transformed to myelodysplastic syndromes (MDS) and acute myeloid leukemia(s-AML). We identified three mutations at CEL-NOS phase, five and seven mutations at MDS and s-AML stages, respectively. Our data illustrate the clonal dynamic process associated with disease evolution from CEL-NOS to s-AML.